Enhancing Brassinosteroid Signaling via Overexpression of Tomato (Solanum lycopersicum) SlBRI1 Improves Major Agronomic Traits - Nie, Shuming; Huang, Shuhua; Wang, Shufen; Cheng, Dandan; Liu, Jianwei; Lv, Siqi; Li, Qi; Wang, Xiaofeng (Frontiers in Plant Science, 2017)
Brassinosteroids (BRs) play important roles in plant growth, development, and stress responses through the receptor, Brassinosteroid-insensitive 1 (BRI1), which perceives BRs and initiates BR signaling. There is considerable potential agricultural value in regulating BR signaling in crops. In this study, we investigated the effects of overexpressing the tomato (Solanum lycopersicum) BRI1 gene, SlBRI1, on major agronomic traits, such as seed germination, vegetative growth, fruit ethylene production, carotenoid accumulation, yield, and quality attributes. SlBRI1 overexpression enhanced the endogenous BR signaling intensity thereby increasing the seed germination rate, lateral root number, hypocotyl length, CO2 assimilation, plant height, and flower size. The transgenic plants also showed an increase in fruit yield and fruit number per plant, although the mean weight of individual fruit was reduced, compared with wild type. SlBRI1 overexpression also promoted fruit ripening and ethylene production, and caused an increase in levels of carotenoids, ascorbic acid, soluble solids, and soluble sugars during fruit ripening. An increased BR signaling intensity mediated by SlBRI1 overexpression was therefore positively correlated with carotenoid accumulation and fruit nutritional quality. Our results indicate that enhancing BR signaling by overexpression of SlBRI1 in tomato has the potential to improve multiple major agronomic traits.